Analisis Pengelolaan Zakat Di Lazis Muhammadiyah (LAZISMU) Kota Medan Berdasarkan Undang-Undang No. 23 Tahun 2011 Tentang Pengelolaan Zakat - Muhammad Arifin Lubis (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This study aims to see the implementation of Law/No. 23/2011 in zakat management, strategies implemented, advantages and disadvantages of LAZIS Muhammadiyah Medan City in zakat management. This research is a qualitative research with field research, conducted at the Amil Zakat, Infaq, and Sedekah Muhammadiyah Institute (LAZISMU) City Medan, which is located on Jl. Mandala By Pass No. 140A. With several informants, namely the Medan City LAZISMU Coordinator, Sharia Council/Supervisory Agency/LAZISMU Management Agency Medan City, Executive Leaders (Directors/Managers), and Amil Division of LAZISMU Medan City. The results of this study are that Lazismu has legality in managing ZIS with a permit from the government, namely the Minister of Religion of the Republic of Indonesia No. 730 of 2016, Lazismu has met the requirements of Law no. 23 of 2011 in the implementation of zakat management. Such as the implementation of productive economic utilization, distribution which is supervised by the supervisory body and sharia board, the existence of zakat calculation services, ZIS receipts, Lazismu separates the bookkeeping of Zakat, infaq, alms and other religious social funds and Lazismu also makes regular monthly reports published in Magazine media. Matahati Lazismu. The advantage of Lazismu is that it can take advantage of the network already owned by Muhammadiyah. The weakness of the Lazismu collection strategy is exacerbated by the failure of Lazismu to maximize the potential of gathering in Muhammadiyah.